HUBUNGAN ANTARA KEMATANGAN KARIR DENGAN KEPUTUSAN PEMILIHAN JURUSAN PENDIDIKAN PADA SISWA KELAS XII - Nasrul, Febriyeni; Fajhriani N, Dyla; Jariah, Nurul; Dwi Januarti, Ulfah; Putra, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the relationship between career maturity and decisions in choosing educational majors among twelfth-grade students. This research used a quantitative approach with a correlational research design. The population in this study consisted of twelfth-grade students, and the data were collected using a questionnaire. The collected data were analyzed using correlation analysis to examine the relationship between career maturity and decisions in choosing educational majors. The results showed that there was a significant relationship between career maturity and decisions in choosing educational majors among twelfth-grade students with a correlation coefficient of 0.62, which is categorized as strong. This indicates that the higher the level of career maturity possessed by students, the better their ability to determine educational majors that are appropriate to their interests, talents, and abilities. Therefore, career maturity is an important factor influencing students’ decisions in choosing educational majors.